Indoor hydroponic farming business plan - Koo, Sey Nee (2018)
Indoor hydroponic farming (IHF) business is starting to draw tractions recently in Malaysia. As of today, there are already a number of players in the market have been involved and started to commercialise the business. Studies have suggested that IHF will be the solution to the urban food security driven by the growth of urban population. Hence, the rise of urban farming.